A novel splice variant of the stem cell marker LGR5/GPR49 is correlated with the risk of tumor-related death in soft-tissue sarcoma patients - Eckert Alexander W; Würl Peter; Greither Thomas; Bache Matthias; Taubert Helge; Rot Swetlana; Schubert Johannes; Vordermark Dirk; Kappler Matthias (BMC Cancer, 2011)
Abstract Background The human leucine-rich, repeat-containing G protein-coupled receptor (LGR) 5, also called GPR49, is a marker of stem cells in adult intestinal epithelium, stomach and hair follicles. LGR5/GPR49 is overexpressed in tumors of the colon, ovary and liver and in basal cell carcinomas. Moreover, an expression in skeletal muscle tissues was also detected. However, there has been no investigation regarding the expression and function of LGR5/GPR49 in soft-tissue sarcomas (STS) yet. Methods Seventy-seven frozen tumor samples from adult STS patients were studied using quantitative real-time TaqMan™ PCR analysis. The mRNA levels of wild type LGR5/GPR49 and a newly identified splice variant of LGR5/GPR49 lacking exon 5 (that we called GPR49Δ5) were quantified. Results A low mRNA expression level of GPR49Δ5, but not wild type LGR5/GPR49, was significantly correlated with a poor prognosis for the disease-associated survival of STS patients (RR = 2.6; P = 0.026; multivariate Cox's regression hazard analysis). Furthermore, a low mRNA expression level of GPR49Δ5 was associated with a shorter recurrence-free survival (P = 0.043). However, tumor onset in patients with a lower expression level of GPR49Δ5 mRNA occurred 7.5 years later (P = 0.04) than in patients with a higher tumor level of GPR49Δ5 mRNA. Conclusion An attenuated mRNA level of the newly identified transcript variant GPR49Δ5 is a negative prognostic marker for disease-associated and recurrence-free survival in STS patients. Additionally, a lower GPR49Δ5 mRNA level is associated with a later age of tumor onset. A putative role of GPR49Δ5 expression in tumorigenesis and tumor progression of soft tissue sarcomas is suggested.